SIMULASI EFEK TURBO CYCLONE TERHADAP KARAKTERISTIK ALIRAN UDARA PADA SALURAN UDARA SEPEDA MOTOR 4 TAK 100 CC MENGGUNAKAN COMPUTATIONAL FLUID DYNAMICS - Muchammad, Muchammad (ROTASI, 2007)
Turbo Cyclone is one of additional devices for internal combustion engine, which can be used to create swirling flows in airchannel. Swirling flow has abilities to improve fuel/air mixing efficiency, increasing combustion intensity and stabilizing thecombustion flame and also rising the flame propagation speed so the complete combustion can be achieved. Turbo Cycloneintallation will affect its air flow characteristics, e.g. turbulence intensity and pressure drop. The blade design has a great effect tothe magnitude of turbulence intensity and pressure drop. The CFD simulation shows that turbo cyclone installation does have effectto the turbulence intensity and pressure drop. Further analysis with blade design variation results that the wider blade angle thebigger its turbulence intensity and pressure drop. Turbo Cyclone with its no-hole blades also has more contribution in rising thosetwo parameters than Turbo Cyclone with holes on its blades. In this case model 7 has the largest turbulence intensity and pressuredrop at all air inlet velocity, 105,32 Pa and 1,52 at air inlet 6,099 m/s, 570,45 Pa and 3,62 at air inlet 14,52 m/s, also 937,73 Pa and4,64 at air inlet 18,634 m/s.